PENGARUH PENAMBAHAN BEKATUL BERAS MERAH TERHADAP SIFAT FISIK, KIMIA, DAN SENSORIS ES KRIM - Lisdyareni, Fransiska Ni Made; Rai Widarta, I Wayan; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
Milk is a food that is consumed by people around the world. Some dairy products that were encountered include ice cream, yogurt, butter, cheese, and others. Ice cream is one type of food that is highly preferred by consumers all ages. The addition of red rice bran is the manufacture of ice cream expected to equip the nutritional content of ice cream, particularly fiber and antioxidants. This research is aimed to determine the effect of red rice bran on physical, chemical, and sensory evaluation of the ice cream. This research used a completely randomized design (CRD) by treatment with the addition of red rice bran (0%, 1,5%, 3%, 4,5%, and 6%) were repeated three times. Data were analyzed by analysis of variance and continued with Duncan’s Multiple Range Test. The result of research showed that the addition of 1,5% red rice bran is the best treatment that gave average value of protein content 2,23%, fat 15,66%, total solid 44,78%, crude fiber content 1,44%, IC 50 0,34 g/kg, overrun 72,85%, resistance 17,79 minutes/10 gram, aroma score rather typical milk, hedonic aroma rather like, color score chocolate of white, color hedonic rather like, texture rather like, flavor score rather sweet, hedonic flavor like, and overall acceptance rather like.
Keywords: ice cream, red rice bran, fiber, antioxidant